Hygiene Predictors among COVID-19 Screened Individuals during the First Wave In Mumbai: A Cross-Sectional Survey - Rujuta Hadaye; Shilpa Nellikka (Healthline, 2022)
Introduction:The most important lesson COVID-19 pandemic thought is basic hygiene practices. It is important to understand hygiene practices among patients during first wave, when meager knowledge about the management of COVID-19 was available. Objective: To assess the adopted behavioral practices and predictors for COVID-19 infection among screened individuals during the 1st wave. Method: A cross-sectional study included COVID-19 screened individuals attending COVID -19 screening OPD at Mumbai. Total 950 participants were interviewed telephonically using convenient sampling method. Logistic regression nanalysis was performed. Results: A total 950 respondents participated, with median age of36 years (range:18yrs to 83 years). Respondents,RTPCR positive or quarantined were 36%. Analysis concludes that practices of having seen or read about hand hygiene, face hygiene, maintaining social distancing, cough etiquettes and enforcement ofstrict lockdown were significantly associated with lower risk of COVID-19 infection (p value <0.05). Conclusion: Hygiene Practices were followed correctly by more than 50% of this cohort however few individuals were able to answer knowledge related questions correctly. Simple hygiene practices like face hygiene, cough etiquettes, social distancing, strict following of lockdown and having seen or read information on hand washing were predictors of COVID-19 infection. The study highlights the need for quick and rigorous attempts to educate people during a state of a health emergency.